Honeymoon-hangover effect: Occupant workspace satisfaction decreases over time - Jing Xiong; Thomas Parkinson; Jungsoo Kim; Richard de Dear (Elsevier, 2024)
This paper investigates the pattern of change in occupants' satisfaction with the Indoor Environmental Quality (IEQ) of their workspace over time. Analyses were performed on a cumulative (2012-2023) database of responses to a Post-Occupancy Evaluation survey in Australia. 20,400 questionnaire responses from 226 office buildings were classified into five groups based on the length of time respondents had occupied their workspace. Associations between workspace satisfaction and the length of time respondents had occupied their workspace were also analysed for different gender and age cohorts. Our results show that occupant satisfaction generally decreased with the length of time they had been allocated to their present workspaces (the 'honeymoon-hangover' effect). People who have occupied their workspace for more than 5 years expressed lower overall satisfaction with their workspace than those who have been there for less than 6 months. The same pattern was observed for occupants' satisfaction with other IEQ dimensions including building image and maintenance, indoor air quality, spatial comfort, and thermal comfort. This 'honeymoon-hangover' effect was evident across genders and age groups. Furthermore, there was negligible difference between the two genders on the 'honeymoon-hangover' effect, although thermal comfort and indoor air quality were generally less satisfactory for women than men. Respondents aged 30 yrs or less showed a larger decline in satisfaction over time compared to those over 50-yrs old. Within the 30-year-or-under age group, occupants who had spent more than 5 years at their workspaces consistently registered the lowest satisfaction score across all IEQ dimensions. Implications and impacts: The findings in this study have significant implications for the design of Post-Occupancy Evaluation (POE) surveys and for facility managers aiming to enhance occupants' satisfaction with their workspace and workplace.